Statistical Analysis of Factors Affecting Utilization of Antenatal Care in Nepal - Shrestha, Gauri; Shrestha, Ganga (Nepal Journal of Science and Technology, 2012)
Antenatal care provides an entry point for pregnant women to the health care system. This study investigates factors associated with the use of maternal health services as number of antenatal care visits. For analyzing the use of antenatal care health services system in Nepal, data were extracted from individual recods of a data file of NDHS 2006. The unit of analysis for this study is Ever Married Woman (EMW) who had at least one live birth in the five years preceding the survey. The sample of study consisted of 4182 EMW. The simple cross tabulation and chi square tests were used for examining the bivariate relationship and multinomial logit (MNL) model was selected for establishing linkage between number of antenatal care visits and several explanatory variables. Estimation of the parameter of this MNL models done by what is known as iteratively weighted leastsquare (IRWLS), which was identical to the algorithm of Fisher scoring and leads to maximize likelihood estimates. The results were interpreted in terms of odd ratios. The result of this study showed that women with low education level, those residing in rural areas and those with low socio-economic status were less likely to use number of ANC visits. DOI: http://dx.doi.org/10.3126/njst.v12i0.6512 Nepal Journal of Science and Technology 12 (2010) 268-275